(untitled) (Research, Society and Development, 2022)
Introduction: The care of child patients is a great challenge in the dental clinic, at first it is difficult to control the child, and later, because caries in the primary dentition presents rapid progression. Objective: This work aims to present a literature review regarding carious lesions in children and the alternative treatment through Papacarie® gel. Methodology: This work was carried out through online bibliographic research of scientific articles. Results: Conventional restorative treatments use rotary instruments and drills, which increase the level of pain, cause discomfort to patients such as anxiety and stress, in addition to the disadvantages of having pulp exposure and removal of healthy tissue. Results and discussions: This technique eliminates the use of local anesthesia, high rotation pens and, finally, absolute isolation, contributing to a better acceptance of patients in the face of treatment as it minimizes the situation of stress with pain and phobia. Conclusion: This method is in agreement with what advocates modern dentistry, which proposes the use of minimally invasive methods, opting for greater preservation of the dental structure.